Protocol for recording physiological signals from the human cerebellum using electroencephalography - Ami Kumar; Yi-Mei Wang; Ming-Kai Pan; Sheng-Han Kuo (STAR Protocols)
Summary: As Purkinje cells of the cerebellum have a very fast firing rate, techniques with high temporal resolution are required to capture cerebellar physiology. Here, we present a protocol to record physiological signals in humans using cerebellar electroencephalography (cEEG). We describe steps for electrode placement and recording. We then detail solutions for dealing with potential muscle, ocular, and electrical artifacts. This protocol has applications in recording patients with cerebellar disorders such as essential tremor, cerebellar ataxia, and dystonia.For complete details on the use and execution of this protocol, please refer to Pan et al.,1 Wong et al.,2 and Wang et al.3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.